2007
DOI: 10.1124/jpet.107.122630
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin (5-HT) in Veins: Not All in Vain

Abstract: The circulatory system consists of veins and arteries. Compared with arteries, veins have been neglected in cardiovascular research. Although veins are significantly less muscular than similarly sized arteries, the contribution of veins to cardiovascular homeostasis cannot be left un-noted because veins accommodate 70% of the circulating blood. Circulating blood platelets contain the majority of systemic 5-HT (5-hydroxytryptamine; serotonin). Similar to venous function, the physiological role of 5-HT in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…Preliminary data from our laboratory revealed that veins were able to take up 5-HT in a significantly larger amount than arteries (Linder et al, 2007). These novel findings suggest that veins, in addition to platelets, may function as a sink for 5-HT in the cardiovascular system.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Preliminary data from our laboratory revealed that veins were able to take up 5-HT in a significantly larger amount than arteries (Linder et al, 2007). These novel findings suggest that veins, in addition to platelets, may function as a sink for 5-HT in the cardiovascular system.…”
mentioning
confidence: 70%
“…5-HT modifies venous tone through direct interaction with venous 5-HT receptors (Cushing et al, 1994;Watts and Cohen, 1999;Watts, 2005;Linder et al, 2007) and indirectly by modifying sympathetic control of venous motor tone . Thus, it is important to understand how 5-HT is handled by venous tissue, as modification in handling could ultimately affect the actions of 5-HT in veins and therefore blood pressure.…”
Section: -Ht In Veinsmentioning
confidence: 99%
“…Platelets are the main source of peripheral serotonin [6,24]. AD has been shown to have increased plasma serotonin levels, which could derive from platelets [25].…”
Section: Serotonin and App In Plateletsmentioning
confidence: 99%
“…Tryptophan crosses the blood-brainbarrier via transporter proteins and acts as the precursor for 5-hydroxytryptamine (5-HT) synthesis in the serotonergic neurons. The cerebral neurotransmitter 5-HT is essential for aggression inhibition (Nelson and Chiavegatto, 2001) and also regulates sleeping, appetite, mood and behavioral activity (Linder et al, 2007;S eve, 1999). Tryptophan has been shown to affect brain and nervous system function through interference with serotonergic neurotransmission.…”
Section: Introductionmentioning
confidence: 99%
“…5-HT plays a major role in appetite, behavioral activity and aggression regulatory mechanism. Therefore, tryptophan deficiency leads to intensification of aggressive behaviors in several animal species and humans (Linder et al, 2007;Miczek and Fish, 2005;Miczek et al, 2002).…”
Section: Introductionmentioning
confidence: 99%